Nurse Competence, Social Influence, and Usability on EMR Use with Perceived Ease as Mediator - Rizqi Kartika Wardani; Rian Adi Pamungkas; Intan Silviana Mustikawati (International Journal of Economics, Commerce, and Management, 2026)
Digitalization in the healthcare sector is a strategic step to enhance efficiency, accuracy, and service quality. One of the key innovations gaining significant attention is the use of Electronic Medical Records (EMR). Purpose: This study aims to analyze nurse competence, social influence, and usability on actual use electronic medical record with perceived ease of use as intervening variable at Satya Negara Hospital. Methods: The research method used a quantitative approach with a cross-sectional design, involving 108 nurses as respondents selected through a saturated sampling technique. Data were collected using a questionnaire and analyzed using a Structural Equation Model (SEM) based on Partial Least Squares (PLS). Findings: The results indicate that nurse competence, social influence, and usability significantly affect the actual use of EMR. Additionally, perceived ease of use mediates these relationships, enhancing the adoption and utilization of EMR systems. Implications: The managerial implications of this study include the need to enhance nurse competency training, strengthen social support in the workplace, and improve the usability of the Electronic Medical Records (EMR) system to encourage more optimal use. This study also contributes to the development of literature on health information technology implementation by integrating human, social, and technical factors into the analytical model.